Rapidly growing proliferative pulmonary chondroma: A case report. (December 2022) - Uchida, Tsuyoshi; Matsubara, Hirochika; Muto, Mamoru; Sugimura, Aya; Onuki, Yuichiro; Nakajima, Hiroyuki
Abstract: Introduction: Pulmonary chondroma, a component of Carney's triad, is commonly unilateral and multiple, and progresses slowly. Herein, we report a case of a chondrogenic tumour that grew and proliferated during follow-up. Presentation of case: A female patient in her 20s presenting with a cough was found to have a 1.4-cm nodule in the left lung on computed tomography (CT). After 18 months' follow-up, CT revealed that the original nodule had increased to 2.2 cm, and a new 1.3-cm nodule had appeared. She was then referred to our hospital and underwent a robot-assisted lower lobectomy of the left lung. The tumour was diagnosed as a chondrogenic tumour. She had no problems after the surgery or during follow-up; other signs of the Carney's triad were ruled out. Twenty-six months postoperatively, there was no evidence of recurrence. Discussion: One report suggests that the growth of pulmonary chondroma is slow, but the present case showed an increase in both the size and number of tumours within 2 years without any symptoms. The chondroma did not recur after the surgery, though her pulmonary tumours had grown and proliferated rapidly. Furthermore, it has been reported that an average of 8.4 years is needed for another sign of Carney's triad to appear; therefore, careful follow-up should be continued. Conclusion: This report suggests that pulmonary chondroma can grow and proliferate rapidly and asymptomatically, and can be controlled by complete resection. Highlights: Pulmonary chondroma can grow and proliferate rapidly and asymptomatically. Pulmonary chondroma can be controlled by complete resection. Pulmonary chondroma is a subset of the Carney's triad. It has been reported to take an average of 8.4 years for the second sign of the Carney's triad to appear.